Communication of Difficult Emotions and Mental States in the Animated Series "Steven Universe" - Drogosz, Anna Maria; Wojtunik, Aleksandra (Acta Neophilologica, 2024)
The aim of this paper is to examine the use of conceptual metaphor in the animated series Steven Universe. We aim to show that the series addresses sensitive issues such as personality disorders, abusive relationships, and the effects of past trauma through the use of conceptual metaphors, both verbal and visual. We believe that conceptual metaphors can help reframe difficult emotional and mental states, which has been recognized in therapy and counselling. We also compare the metaphors identified in therapeutic discourse with those found in the series.